2018
DOI: 10.1371/journal.pone.0195801
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards and knowledge about Human Papillomavirus (HPV) and the HPV vaccination in parents of teenage boys in the UK

Abstract: The incidence of cancers attributable to Human Papillomavirus (HPV) that affect males is on the rise. Currently in the UK teenage boys are not vaccinated against HPV while teenage girls are. The rationale for not vaccinating boys is that vaccinating girls should provide herd immunity to boys, however this does not protect men who have sex with men or men who have sex with unvaccinated women. The issue of whether to vaccinate boys or not is a controversial one with considerable lobbying taking place to change t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 21 publications
5
29
1
Order By: Relevance
“…The important role of the level of knowledge has been already reported. 29,38 In addition, it was found that parents who needed information were more likely to be hesitant. These results support the existing literature, regarding a relationship between needing more information and being hesitant.…”
Section: Discussionmentioning
confidence: 99%
“…The important role of the level of knowledge has been already reported. 29,38 In addition, it was found that parents who needed information were more likely to be hesitant. These results support the existing literature, regarding a relationship between needing more information and being hesitant.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered that conducting common, systematic, and continuous health education programs aimed at both sexes and including both parents, which would increase knowledge and awareness on HPV and the HPV vaccine, and provide positive attitudes, will be effective in protecting people against HPV-related cancers (17,31,33,34,36,38). In addition, it will be an important initiative for the protection of public health that healthcare authorities include HPV vaccines in their immunization programs and that policies encourage acceptance of the vaccine in society in countries where the HPV vaccine is not included in national vaccination schedules.…”
Section: Discussionmentioning
confidence: 99%
“…In information and awareness studies on HPV and the HPV vaccine that were conducted in developed countries, it was reported that HPV knowledge and awareness were at low-tomoderate levels, and vaccination rates (26%-55%) were not at desired levels, although the willingness for vaccination was high (17,(28)(29)(30)(31)(32)(33)(34). In studies conducted in developing countries, it was reported that HPV knowledge and awareness and willingness for vaccination were at low-to-moderate levels, and HPV vaccination rates were quite low (13.3%-16.1%) (35)(36)(37)(38)(39)(40)(41).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…11 In addition to parents, healthcare providers play a crucial role in ensuring its administration. [21][22][23][24][25][26][27][28] It is important for healthcare providers to bundle HPV vaccines with other required vaccines, such as tetanus-diphtheria-pertussis (Tdap) and meningococcal vaccine (MCV4, MenB). 29,30 They are encouraged to consistently and equally recommend HPV vaccination to parents of female and male children.…”
Section: Introductionmentioning
confidence: 99%
“…20 Interventions that improve parental knowledge and awareness prior to the administration of the HPV vaccine have increased uptake immediately following the encounter. 24,36,37 The sex of the parent may also affect the choice to vaccinate. Male parents are less likely to vaccinate their daughters.…”
Section: Introductionmentioning
confidence: 99%